OCCUPATIONAL THERAPHY DEPICTION IN PATIENTS WITH HALLUCINATIONS: LITERATURE REVIEW: TERAPI OKUPASI MENGGAMBAR PADA PASIEN HALUSINASI : LITERATURE REVIEW - Widyaningtyas, Ryka; Kandar, Kandar (Essential English Grammar, 2025)
Hallucinations are one of the most common sensory perception disorders in patients with mental disorders, particularly schizophrenia. One non-pharmacological therapy that can be used to reduce hallucination symptoms is occupational drawing therapy. This study aims to analyze the effectiveness of occupational drawing therapy in reducing hallucination signs and symptoms through a literature review method. Literature searches were conducted using the Google Scholar database with relevant keywords and article selection was based on inclusion and exclusion criteria. The results show that occupational drawing therapy significantly reduces hallucination symptoms in patients, both in terms of symptom intensity reduction and changes in patient conditions. This therapy helps patients express emotions, distraction from hallucinations, and improve self-control. Therefore, occupational drawing therapy can be considered an effective non-pharmacological intervention for managing patients with hallucinations.